Clinical staff reported knowledge on the existence of clinical governance protocols or tools utilised in selected South African hospitals. - Nomfuneko Sithole; Wezile W Chitha; Onke R Mnyaka; Akhona B A Ncinitwa; Sibusiso C Nomatshila; Xolelwa Ntlongweni; Kedibone Maake; Bongiwe E Mkabela; Ntiyiso V Khosa; Ziyanda B Ngcobo; Nombulelo Chitha; Khanyisile Masuku; et al. (PLoS ONE)
Introduction Clinical governance outlines duties and responsibilities as well as indicators of the actions towards best possible patient outcomes. However, evidence of outcomes on clinical governance interventions is limited in South Africa. This study determined knowledge of clinical staff about the existence of clinical governance protocols/tools that are utilised in selected South African hospitals. Methods A cross-sectional study conducted among randomly sampled clinical staff at Nelson Mandela Academic (NMAH), St Elizabeth in the Eastern Cape Province and, Rob Ferreira (RFH) and Themba Hospitals in the Mpumalanga Province of South Africa. A self-administered survey questionnaire was used to collect demographic information and quality improvement protocols/tools in existence at the hospitals. Data were captured in Excel spreadsheet and analysed with STATA. Knowledge was generated based on the staff member's score for the 12 questions assessed. Results A total of 720 participants were recruited of which 377 gave consent to participate. Overall, 8.5% (32/377) of the participants got none or only one correct out of the 12 protocols/tools; and 65.5% (247/377) got between two and five correct. The median knowledge scores were 41.7% (interquartile range (IQR) = 16.7%) in three of the hospitals and 33.3% (IQR = 16.7%) at NMAH (p-value = 0.002). Factors associated with good knowledge included more than five years of experience, being a professional nurse compared to other nurses, not working at NMAH as well as being a medical doctor or pharmacist compared to other staff. Overall, 74.0% (279/377) of the respondents scored below 50%; this was 84.4% (92/109) at NMAH and 66.3% (55/83) at RFH and this difference was statistically significant (p-value = 0.017). Conclusion Despite clinical governance implementation, there was low knowledge of clinical governance protocols/tools among clinical staff. Therefore, providing more effective, relevant training workshops with an emphasis on importance of local ownership of the concept of clinical governance, by both management and clinical staff is of great importance.